1981
DOI: 10.1080/03749444.1981.10736614
|View full text |Cite
|
Sign up to set email alerts
|

Researches on the Coast of Somalia. The Shore and the Dune of Sar Uanle

Abstract: Colour: body and legs reddish-brown marbled with green. Claws external face red, tips and internal face white. Ecology: exposed rocky shores usually on cliffs. Distribution: Indo-Pacific area and from the Red Sea to Natal on the African coast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…A morphological comparison of the collected specimens of Perisesarma from East Africa revealed that two distinct species were indeed present. One of the two forms agreed perfectly with previous descriptions of the mangrove crab P. guttatum (A. Milne Edwards, 1869) (see Crosnier, 1965; Vannini & Valmori, 1981). The other form seemed to be diagnostic in the following characters: a conspicuous blue colour on the lateral and frontal regions of the crab combined with a mottled blue on the otherwise dark carapace and dorsal surfaces of the legs.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…A morphological comparison of the collected specimens of Perisesarma from East Africa revealed that two distinct species were indeed present. One of the two forms agreed perfectly with previous descriptions of the mangrove crab P. guttatum (A. Milne Edwards, 1869) (see Crosnier, 1965; Vannini & Valmori, 1981). The other form seemed to be diagnostic in the following characters: a conspicuous blue colour on the lateral and frontal regions of the crab combined with a mottled blue on the otherwise dark carapace and dorsal surfaces of the legs.…”
Section: Resultssupporting
confidence: 88%
“…Bright & Hogue, 1972; Hartnoll, 1975; Micheli, Gherardi & Vannini, 1991; Cannicci et al ., 1996; Ruwa, 1997; Slim et al ., 1997; Dahdouh‐Guebas et al ., 1999; Fratini, Cannicci & Vannini, 2000; Flores, Paula & Dray, 2003). Currently, there is only one species of Perisesarma , P. guttatum , attributed to East Africa (Crosnier, 1965; Hartnoll, 1975; Vannini & Valmori, 1981), whereas there have been 19 species reported within the Indo‐Pacific region as a whole (Davie, 2003). Given the long planktonic phase of East African species of Perisesarma (22–25 days, see Pereyra Lago, 1993), and the presence of strong oceanic currents in the Indian Ocean (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the majority of the literature dealing with P. guttatum most likely includes both species (Gillikin & Schubart, 2004). Perisesarma guttatum is endemic to East Africa, occurring from Somalia down to the north coast of South Africa, in Madagascar and in the Red Sea (Vannini & Valmori, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Since Rathbun (1909) described I. paludicola from Thailand, this species has been reported from Madagascar (Crosnier, 1965), Mozambique (Barnard, 1955, as I. rhizophorae; Kensley, 1981), Tanzania (Hartnoll, 1975), Somalia (Vannini et al, 1981), the Red Sea (Fishelson, 1971), Ethiopia and the Sinai Peninsula (Holthuis, 1977), Karachi (Tirmizi, 1985), Thailand (Rathbun, 1909), New Caledonia , and Kumamoto (Yamaguchi et al, 1976). Since Crosnier (1965) synonymized I. rhizophorae (Barnard, 1955) with I. paludicola, successive authors followed Crosnier (1965) and considered all Ilyograpsus crab to be I. paludicola, until T. Sakai (1983) described I. nodulosus from the Ryukyu Islands.…”
Section: Discussionmentioning
confidence: 96%